Teneligliptin add on to monotherapy treatment in patients with type 2 diabetes - Chatterjee, Amitesh Kumar (International Journal of Research in Medical Sciences, 2018)
Background: In patient with type 2 diabetes (T2D) inadequately controlled on monotherapy, teneligliptin is efficacious and safe as add-on to treatment with oral antidiabetic drugs (OADs) or insulin. Data on efficacy of teneligliptin in Indian patients is relatively sparse. Aim of the study was to assess the efficacy of teneligliptin used as add-on treatment in patients inadequately controlled on monotherapy with OADs or insulin. Methods: We retrospectively evaluated the electronic database at our endocrinology clinic from East India. Patients who were treated with teneligliptin (20 mg/day) as add-on to monotherapy with OADs or insulin were identified, and data analysed. Primary assessment parameters were change in glycosylated haemoglobin (HbA1c %), fasting plasma glucose (FPG, mg/dL) and post-prandial plasma glucose (PPG, mg/dL) over 12-week from the addition of teneligliptin. Paired t test and McNemar test applied to derive statistical significance of paired continuous and categorical variables respectively. Results: In 88 patients, teneligliptin was used as add-on treatment in 77.3% and 22.7% patients receiving OAD and insulin as monotherapy respectively. Mean age of population was 48.3±15.1 years and 67% were males. From baseline to 12-weeks, there was significant change in HbA1c (9.6±2.1 to 8.4±1.2%, P<0.001), FPG (181.4±54.5 to 140.9±27.1 mg/dL, P<0.001) and PPG (273.7±75.6 to 201.1±47.7 mg/dL, P<0.001). Reduction in these glycemic parameters was significant in patients with teneligliptin as add-on to either OADs or insulin. Overall, 12.5% patients reached the target HbA1c of <7% after 12-week treatment (P=0.004). Conclusions: In patients who are uncontrolled on monotherapy with either OADs or insulin, addition of teneligliptin resulted in significant reduction of HbA1c, FPG and PPG after 12-week treatment. This establishes usefulness of teneligliptin in Indian patients with T2D. A larger, randomized, comparative study with other gliptins is warranted.